Analisis Pengaruh Kecukupan Modal, Likuditas, Risiko Kredit dan Efisiensi Biaya Terhadap Profitabilitas Bank Umum - Erric Wijaya; Aulia Wahyuning Tiyas (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
The national economy is experiencing a slowdown in the third quarter of 2015, the bank’s performance also weakened with the economic downturn. In terms of profitability, pressure bank earnings are also expected to continue. Banks are expected to still be experiencing a slowdown in profit growth. The purpose of this study is to examine, analyze and deduce the effect of capital adequacy ratio, liquidity ratio, credit risk and efficiency ratios ROA charges against Indonesian commercial banks that went public during the period 2011-2015. The study population is an Indonesia commercial bank which goes public 2011-2015. The number of samples in this study was 40 banks with the dependent variable Return On Asset (ROA) as well as the independent variable Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR, Non-Performing Loan (NPL) and Biaya Operasional Pendapatan Operasional (BOPO). The method used in this research is the Linear Regression Analysis and t-test with a significance level of 5% and processed using EViews 7.1. The results of this study indicate that the NPL of significant positive effect on ROA commercial banks to go public the period 2011-2015. BOPO significant negative effect. CAR and LDR no significant positive effect on commercial banks to go public ROA period 2011-2015. The results of this study have implications for the management, practitioners, and academic communities, namely the need to consider the relationship of NPL, ROA, CAR, and LDR to ROA companies.